Pengaruh Kompensasi Terhadap Kinerja Karyawan Melalui Prestasi Kerja Karyawan pada PT. Nippon Paint Kediri - Saputra, Beny Mahyudi (Akutansi Bisnis & Manajemen ( ABM ), 2019)
The objectives of this study are: 1). Knowing the effect of compensation on employee performance directly. 2). Knowing the effect of compensation on employee performance. 3). Knowing the effect of work performance on employee performance. 4). Knowing the effect of compensation on employee performance through work performance. The population is defined as "the number of families that will be studied", the population used by researchers in this study is the entire work of PT. Nippon Paint Kediri. This research sample was taken by using simple random sampling technique that is sampling technique from the population that was carried out randomly regardless of the strata that existed in the population. simple random sampling is a method of sampling where each element of the population has the same opportunity to be chosen as a member of the sample and the sample is taken using a number table/generator. The technique used is path analysis. Based on the results of the research and the discussion described, conclusions can be drawn as follows: 1). There is a significant direct effect between the variable compensation (X1) on employee performance (X2) of 0.410. 2). There is a significant direct effect between compensation (X1) on employee performance (Y) of 0.561. 3). There is a direct significant between employee work performance (X2) on employee performance (Y) of 0.358. 4). There is an indirect effect between compensation (X1) on employee performance (Y) through employee work performance (X2) of 0.708.